LEGAL PROTECTION OF UNDERAGE CHILDREN AS VICTIMS OF VIOLENT CRIMINAL ACTS - Permana Ihtiar; Herwin Sulistyowati; Imam Alghozali Hide Wulakada (PT Akselerasi Karya Mandiri, 2023)
This research aims to find out the legal protection for children as victims of violence according to Law Number 35 of 2014 concerning child protection and to determine judges' considerations in imposing crimes on cases of violence against children in Decision Number 253/Pid. Sus / 2021 / PN Jap. The results of this study are cases of violence that caused death in Criminal Decision Number 253/ Pid. Sus /2021/PN Jap, so it can be seen that there is a denial of Article 26 paragraph 1 of the UUPA, that parents have a responsibility to their children to care for, care for, educate and protect children. The judge's considerations in imposing a sentence are divided into two matters, namely juridical concerns and non-juridical considerations. Juridical considerations are based first on the prosecution's indictment, testimony, witness statements, evidence, and articles in criminal law, namely Article 76C RI Law NO.35 of 2014 concerning Child Protection. While the non-juridical considerations are related to mitigating and aggravating circumstances, namely, the aggravating circumstances of the defendants are the defendants' actions resulting in the child's death and the defendant is the child's biological father (victim). Meanwhile, the mitigating circumstances were that the defendant admitted his actions and was polite in court. Suggestions in this study are that the central government, regional governments, and other state institutions related to child protection (KPAI) must carry out good supervision to carry out socialization regarding all provisions of laws and regulations relating to child protection. Repeated violence should be carried out viciously as an aggravating circumstance to sentence Rubenson to a maximum of 15 years in prison under the provisions of Article 80 paragraph (3) of Law Number 35 of 2014 concerning child protection.